Achieving a full color palette with thickness, temperature, and humidity in cholesteric hydroxypropyl cellulose - Ren, Hongning; Balcerowski, Tadeusz; Dumanli, Ahu Gümrah (Frontiers in Photonics, 2023)
Hydroxypropyl cellulose (HPC) is a sustainable, cost-efficient, and bio-compatible cellulose derivative that forms cholesteric liquid crystalline phases in highlyconcentrated water solutions that reflects colour in the visible range. While there have been studies exploiting HPC’s structural coloration and transferring the cholesteric order of the solutions into solid form via cross-linking, there is still lack of understanding on the thermotropic mechanisms that enable the transfer of the structural ordering of the pure HPC at higher temperatures. In this work, we demonstrate the balance between the temperature, humidity, and film thickness to achieve a full color palette of pure HPC. We reveal that at the early stages of the evaporation, formation of a dense skin over the lyotropic phase facilitates the thermal expansion of the HPC during the heat treatment. Increasing the thickness, applying higher drying temperatures, and exposing the samples to higher humidity during the evaporation all result with increased pitch values that cause a red-shift in coloration in the solid state. Our analysis of the HPC samples dried in controlled temperature and humidity conditions at a fixed thickness provided an understanding of the dominance of the thermal expansion which drives the final structural organization in the solid cholesteric phase. When the thickness of the films was varied against fixed temperature and humidity conditions, the color shift from red to violet follows the thickness gradient of the sample due to the change in the drying time required to reach the solid form.